Distinct prelimbic cortex ensembles encode response execution and inhibition - Rajtarun Madangopal; Yuan Zhao; Conor Heins; Jingfeng Zhou; Bo Liang; Giovanni Barbera; Ka Chun Lam; Lauren E. Komer; Sophia J. Weber; Drake J. Thompson; Yugantar Gera; Diana Q. Pham; et al. (Proceedings of the National Academy of Sciences, 2025)
Learning when to initiate or withhold actions is essential for survival, requiring the integration of past experiences with new information to adapt to changing environments. The prelimbic cortex (PL) plays a central role in this process, with a stable PL neuronal population (ensemble) recruited during operant reward learning to encode response execution. However, it is unknown how this established reward-learning ensemble adapts to changing reward contingencies, such as reward omission during extinction. Specifically, does the same ensemble adjust its activity to support behavior suppression, or is a distinct ensemble recruited for this new learning? Our data reveal that operant extinction learning recruits a distinct PL Extinction ensemble to support response inhibition, and concerted engagement of both ensembles encodes both ongoing and subsequent context-specific behavior. Using single-cell calcium imaging, we longitudinally tracked PL neurons in rats as they pressed a lever for food rewards (Training), learned to suppress responding upon reward omission (Extinction), and reinstated responding following a noncontingent “priming” pellet (Reinstatement). We trained decoders on individual rats’ PL activity patterns to predict trial-wise responses and used an in silico deletion approach to identify separate PL Training and Extinction ensembles associated with response execution and inhibition, respectively. Critically, both ensembles were reengaged and maintained their distinct roles during Reinstatement. These findings highlight ensemble-based encoding of multiple, even opposing, learned associations within the same region, demonstrating how selective ensemble recruitment enables behavioral flexibility under changing contingencies.